Accuracy of the Translation of the Indonesian Short Story "Angsa dengan Telur Emas" Into English Using U-Dictionary - Basar Lolo Siahaan; Novita Gresiana Manurung; Oktavianti Sianturi; Miranda Sinaga (Journal on Education, 2023)
This research was focused on the extent of the accuracy of the translation of the Indonesian Short Story “ Angsa dengan Telur Emas" into English Using U-Dictionary. The short story “Angsa dengan Telur Emas" of translation were analyzed from Using U-Dictionary.Theories used in this research was Nababan (2012) Scale for scoring accuracy divided into 3 namely accurate, less accurate, inaccurate. This research was conducted using a descriptive qualitative method and the objective of the research is to find out the level of accuracy of the translation of the Indonesian short story “Angsa dengan Telur Emas" into English using U-Dictionary. After conducting the analysis, this research showed the accurate, less accurate and inaccurate. And the kinds of inaccurate divided 4 namely, mistranslation, omission, addition and un-translated According Specia and Shah (2014). They were 182 data as samples. The accuracy percentage was 48, 35%. The less accurate percentage was 17, 58%.The inaccurate percentage was 34, 06 %. After calculating the average accuracy level, the result showed that Short Story “Angsa dengan Telur Emas” Using U-Dictionary was considered as accurate translation.